Evaluation of a national digital pre-implantation biopsy service for deceased-donor kidney transplantation in the UK (Pithia trial); a stepped-wedge cluster randomised registry trialResearch in context - Dominic M. Summers; John O.O. Ayorinde; Desley A. Neil; Karla Hemming; Laura Smith; Jennifer Mehew; Helen Thomas; Rosie Brown; Suzie Phillips; Emma Laing; Anna Sidders; Alison J. Deary; et al. (The Lancet Regional Health. Europe)
Summary: Background: Pre-implantation biopsy may help select kidneys retrieved from elderly deceased donors for transplantation, but concerns persist that it may cause unnecessary discard of kidneys that would have provided acceptable transplant function. The PITHIA trial tested the hypothesis that introduction of a National Digital Pathology Service (NDPS) would increase the proportion of kidneys transplanted from elderly donors and/or improve their function. Methods: A stepped-wedge cluster randomised controlled registry trial delivered the NDPS to 22 UK kidney transplant centres (clusters) in 5 sequences at four-monthly intervals, using a restricted randomisation technique to ensure similar cluster sizes in the intervention and control status. Upon access to the intervention, centres could request urgent pre-implantation biopsy on kidneys from deceased donors aged 60 years or older. Co-primary outcome measures were the proportion of kidneys transplanted upon first offer according to whether the centre had access or not to the biopsy service, and the 1-year eGFR of the kidneys that were transplanted. Analysis adjusts for clustering and underlying secular trends, with 97.5% Confidence Intervals (CI) reported to reflect the two co-primary outcomes. The trial is complete (Trial Registration Number: ISRCTN 11708741). Findings: The trial commenced on 1st October 2018 and ended on 31st January 2022. Of the 2502 eligible kidneys offered, 1355 single and 67 dual transplants were performed. Regarding the first primary endpoint, a non-significantly lower proportion of those kidneys first offered to centres with access to the biopsy service were transplanted compared with those offered to centres without access (295 of 1241 (23.8%) vs. 377 of 1261 (29.9%): adjusted Odds Ratio (97.5% CI) 0.91 (0.60–1.39); p = 0.6083). For the second primary endpoint, the adjusted mean (SE) 1-year eGFR of the transplant kidneys was similar, irrespective of whether the implanting centre had access to the biopsy service or not (43.7 (1.3) ml/min/1.73 m2 vs. 42.2 (1.3) ml/min/1.73 m2; adjusted mean difference (97.5% CI) 1.53 (−2.33 to 5.40); p = 0.37). Secondary outcome analysis of how the biopsy service was adopted revealed that biopsies were performed on 287 of the 1493 (19.2%) kidneys offered to at least one centre with access to the biopsy service, with marked variation between transplant centres in requests for biopsy, and in implantation rates of biopsied kidneys. Nevertheless, 191 (66.6%) of biopsied kidneys were transplanted, compared with 643 of the 1009 (63.7%) kidneys only ever offered to centres without biopsy access, and 588 of the 1206 (48.8%) kidneys that were not biopsied, despite being offered to at least one centre with biopsy access. Interpretation: Implementation of the NDPS did not significantly increase transplantation rates of elderly deceased donor kidneys upon first offer, nor improve 1-year eGFR of the transplanted kidneys. This may reflect inter-centre variation in adoption and application of the biopsy service; such variations would need to be considered when designing future studies of pre-implantation biopsy analysis. Funding: NIHR Research for Patient Benefit programme (RfPB PB-PG-1215-20033).